Pliocene corals from the Togopi Formation of the Dent Peninsula, Sabah, northeastern Borneo, Malaysia. Issue 2 (3rd April 2019) - Saw, Jasmin V.M.; Hunter, Aaron W.; Johnson, Kenneth G.; Abdul Rahman, Abdul Hadi B.
Abstract : Saw, J.V.M., Hunter, A.W., Johnson, K.G. & Abdul Rahman, A.H.B., November 2018. Pliocene corals from the Togopi Formation of the Dent Peninsula, Sabah, northeastern Borneo, Malaysia. Alcheringa 43, 291–319. ISSN 0311-5518 The palaeobiology of the Malay Archipelago region remains poorly documented, despite its present-day significance as a modern global marine biodiversity hotspot. The Togopi Formation of the Dent Peninsula, situated in Borneo on the western Sulu Sea and eastern coast of Sabah, Malaysia, preserves Plio-Pleistocene sedimentary sequences interpreted to represent localized transgressive episodes, and which have a relatively high coral diversity. Fossil corals were sampled from three available quarries on the Dent Peninsula, the sediments of which have been previously dated as 4.5–3.4 Ma in age based on foraminiferal data and radiometric analyses. These Pliocene corals are identified here based on their macromorphology, micromorphology and microstructural characteristics. In total, this study describes 28 fossil coral taxa, with 16 genera recognized and 22 taxa identified to species level, 21 of which can be confidently assigned to extant species. These new data have resulted in revised stratigraphic ranges for eight of these species. As the most comprehensive systematic survey of corals from the Pliocene of the Indo-Pacific to date, this study indicates a high diversity of corals on the margin of the Sabah Sea, Borneo, at this time, including taxa found today, thus casting doubt on the local impact of the Plio-Pleistocene extinction previously reported from faunal analyses of the central Indo-Pacific. Jasmin V.M. Saw[varnmay@yahoo.com ] Department of Petroleum Geosciences, Universiti Teknologi PETRONAS, 32610 Seri Iskandar, Perak, Malaysia; Aaron W. Hunter*[awh31@cam.ac.uk ] Department of Earth Sciences, University of Cambridge, Downing Street, Cambridge CB2 3EQ, UK; Kenneth G. Johnson[k.johnson@nhm.ac.uk ] Department of Earth Sciences, The Natural History Museum, Cromwell Road, London SW7 5BD, UK; Abdul Hadi B Abdul Rahman[hadi_rahman@utp.edu.my ] Department of Petroleum Geosciences, Universiti Teknologi PETRONAS, 32610 Seri Iskandar, Perak, Malaysia. *Also affiliated with: School of Earth Sciences, The University of Western Australia, 35 Stirling Highway, Crawley, WA 6009, Australia.